Extracurricular Sports Achievements of Students at SMAN 1 Manganitu Selatan, Sangihe Islands Regency - Katuuk, Ariel; Lumapow, Harol R.; Mongdong, Romi (JR Education, 2025)
This study aims to describe and analyze student achievement in extracurricular sports activities at SMA Negeri 1 Manganitu Selatan, Sangihe Islands Regency. Extracurricular sports activities are an important part of developing students' potential, character, and non-academic skills. The method used is a qualitative descriptive approach with data collection techniques through observation, interviews, and documentation. The study results show that students actively participate in various sports such as football, volleyball, and athletics, and have achieved success at the school, district, and several provincial levels. Supporting factors for achievement include student enthusiasm, support from mentoring teachers, and adequate training facilities. However, there are also obstacles like limited facilities, lack of funds, and limited training time. This study concludes that despite the challenges, extracurricular sports activities at SMA N 1 Manganitu Selatan have made a positive contribution to character building and improving student achievement.